Pizza dreams do come true - Higgins, Cam; Steinfeld, Allison (New York : Little Simon, 2025)
When Ratnip and his sister Anchovy cannot find any pizza in the trashcans of the city, they gather their other siblings, Pepperoni, Marg, and Veggie, to make a whole pizza of their own.